Studi Eksplanatori-Konfirmatori Tanggung Jawab Guru Kristen Sebagai Pelayan Tuhan Berdasarkan 1 Timotius 4:1-16 - Yoel Triyanto; Hana Suparti; Sri Wahyuni; Andreas Fernando (Vox Dei: Jurnal Teologi dan Pastoral, 2022)
Believers as servants of God have a responsibility to properly instill the teachings of Scripture as a filter of the teachings that develop around them. Being a true and exemplary servant of Christ is the advocate of every believer. The ability to carry out the responsibilities of God's servants became a necessity for Christian teachers. This study aims to examine the implementation of the responsibility of Christian teachers as ministers of God based on 1 Timothy 4:1-16. The research was conducted quantitatively using explanatory-affirmative analysis on Christian teachers in Tangerang. The results showed: 1. The degree of implementation of responsibility in the moderate category, 2. The most dominant dimension in the implementation of responsibility is to be exemplary, 3. The length of the teacher's teaching period affects the level of implementation of responsibilities. From the results of this study, Christian teachers in Tangerang need to improve the implementation of the responsibility of God's servants and develop quality so that they can be exemplary and increase activities that develop teaching skills.